THE ROLE OF AGRICULTURAL SECTOR IN BANTUL REGION DEVELOPMENT - Arumsari, Vini; Rini, Wulandari Dwi Etika (Universitas Sebelas Maret, 2010)
This research is aimed to find out the ability of agricultural sector in supporting government’s development and the role of agricultural sector in the development of Bantul region. This research uses descriptive method. In deciding the research site, the research uses purposive method. The data used in this research is the annual time series data within 2005-2007. Carrying capacity ratio analysis is used to analyze the data regarding the ability of a certain region is supporting food availibility, which scaling the amount of the owned land in a certain region and the population within, whereas everything deal with agricultural sector in developing Bantul region is analyzed by calculating the Regional Domestic Gross Product percentage of agricultural sector, which scaling the agricultural sector Regional Domestic Gross Product and all sector Regional Domestic Gross Product. The result of this research showed that average value of Bantul Region’s Carrying Capacity Ratio during 2005-2007 is 1,46. The result for the agricultural sector’s rule in supporting the development of Bantul Region showed that agricultural sector is playing a major rule, with its highest percentage during 2005-2007 for 24,49% or >11,11%, which means that agricultural is the main sector in contributing the Regional Domestic Gross Product of Bantul Region.